녹용 물 추출물의 파골세포 분화 억제효과 - 곽한복(Han Bok Kwak); 김주호(Ju Ho Kim); 김동주(Dong Joo Kim); 권영미(Young Mi Kwon); 오재민(Jae Min Oh); 김윤경(Yun Kyung Kim) (동의생리병리학회지, 2008)
Natural substances have recently received much attention as therapeutic drugs to prevent many diseases in humans because they avoid the many side effects of treatment with chemical compounds. We examined the effect of water extract of deer antler in RANKL-induced osteoclast differentiation. The effects of water extract of deer antler in osteoclast differentiation were determined by culture of bone marrow macrophages (BMMs). The mRNA expression levels of c-Fos, NFATc1, TRAP, and GAPDH in BMMs were analyzed by RT-PCR. Cell lysates were obtained from the treated cells, the expression levels of c-Fos and NFATc1 were determined by western blotting with antibodies for c-Fos and NFATc1. Water extract of deer antler greatly inhibited RANKL-mediated osteoclast differentiation in osteoclast precursors without cytotoxicity. Water extract of deer antler inhibited the expression of c-Fos and NFATc1 in BMMs treated with RANKL. Our findings suggest that water extract of deer antler inhibited osteoclast differentiation by suppressing c-Fos and NFATc1 expression in response to RANKL. These results demonstrate that water extract of deer antler may be a useful the treatment of bone-related disease such as osteoporosis.